Role of radial electric field in LH transition triggered by counter-NBI at low plasma Density in the TUMAN-3M tokamak - Tukachinsky, A.S.; Askinazi, L.G.; Chernyshev, F.V.; Golant, V.E.; Irzak, M.A.; Kornev, V.A.; Krikunov, S.V.; Krupnik, L.I.; Lebedev, S.V.; Melnik, A.D.; Razumenko, D.V.; Rozhdestvensky, V.V.; et al. (Вопросы атомной науки и техники, 2008)
Threshold power needed to attain H-mode in a tokamak is a critical parameter for designing of future devices and in particular fusion reactor ITER [1]. According to commonly accepted scaling [2] the threshold power Pthr increases with average density ne when the density exceeds some ne min at which Pthr is minimal. An increase in the Pthr towards low density was observed in many experiments [3-6], prevents the transition at lower ne as well. Physics of the threshold power increase at low ne is not well understood. Since the radial electric field Er and Er×B sheared flow play important roles in the LH transition one could expect these quantities effect the low transitions. Toroidal rotation and radial electric field generation during counter-NBI have been studied in [7] and recently reconsidered theoretically in [8]. Thus, motivation for the presented study is to analyze effect of counter-NBI on the LH transition at low density.